Komite Persiapan Penegakan Syariat Islam: A South Sulawesi Formalist Islamic Movement - Juhanis, Hamdan (Studia Islamika, 2007)
This article has examined the dynamics of the formation of KPPSI, its emergence and the character of its supporters. It can be concluded that the legacy of DI is clearly observable in the former DI followers - who supported the establishment of the movement. Aziz Kahar Muzakkar is the son of Kahar Muzakkar. However, the DI factor cannot wholly explain the emergence of KPPSI. This discussion has shown that there were many other Islamists in KPPSI who had no DI ties. This attests to the continuing influence of Islamic modernism, including the role of Muhammadiyah educational training in the radicalization of Islamism in the region. Furthermore, young Islamists have begun to be shaped by broader Islamist movements due to their access to global Islam. To some extent, KPPSI also attracted young activists with attitudes of intolerance to others.DOI:Â 10.15408/sdi.v14i1.557